AN ANALYSIS OF GRAMMATICAL ERRORS OF USING GOOGLE TRANSLATEFROM INDONESIA TO ENGLISH IN WRITING NARRATIVE TEXT - Azura Srikandi; Sholihatul Hamidah Daulay (XXXXXXXX, 2022)
This study focuses on the grammatical errors made by GoogleTranslate in translating narrative text from Indonesian to English.Thenarrative text is a text written by class X culinary arts studentsat SMKTunas Karya Batang Kuis. The research method used in conductingthis research is qualitative with content analysis as the researchdesign. It is also known as the document analysis method.It is intendedthat readers will be able to learn about the types of grammar errorsthat occur when using Google Translate and also the most commonerrors. This research discovered that there are two addition errors infive narrative texts. The words are "after and who." There are twodeletion errors. Those are deletion articles and translated people'snames. Replacement errors are the most common, followed by a totalof 17 errors. Among them are replacement errors because theycannot find the right equivalent, translating word for word, pronounsubstitution errors, and translating people's names. The last is amisordering error. There are two misordering errors: that a word ora group of words is placed incorrectly in a sentence. It is intendedthat once readers understand this, they will avoid making the sameerrors and enhance their grammar translation knowledge and skills.Keywords: Google translate, Grammatical errors,Narrative text